Delivering culturally appropriate residential rehabilitation for urban Indigenous Australians: a review of the challenges and opportunities - Taylor, Kate; Thompson, Sandra; Davis, R. (Blackwell Publishing Asia, 2010)
Objective: To review the challenges facing Indigenous and mainstream services in delivering residential rehabilitation services to Indigenous Australians, and explore opportunities to enhance outcomes. Methods: A literature review was conducted using keyword searches of databases, on-line journals, articles, national papers, conference proceedings and reports from different organisations, with snowball follow-up of relevant citations. Each article was assessed for quality using recognised criteria. Results: Despite debate about the effectiveness of mainstream residential alcohol rehabilitation treatment, most Indigenous Australians with harmful alcohol consumption who seek help have a strong preference for residential treatment. While there is a significant gap in the cultural appropriateness of mainstream services for Indigenous clients, Indigenous-controlled residential organisations also face issues in service delivery. Limitations and inherent difficulties in rigorous evaluation processes further plague both areas of service provision.Conclusion: With inadequate evidence surrounding what constitutes ‘best practice’ for Indigenous clients in residential settings, more research is needed to investigate, evaluate and contribute to the further development of culturally appropriate models of best practice. In urban settings, a key area for innovation involves improving the capacity and quality of service delivery through effective inter-agency partnerships between Indigenous and mainstream service providers.